2013
DOI: 10.1016/j.febslet.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the two domains of E. coli 5′‐nucleotidase to substrate specificity and catalysis

Abstract: a b s t r a c tEscherichia coli 5 0 -nucleotidase, a two-domain enzyme, dephosphorylates various nucleotides with comparable efficiency. We have expressed the two domains individually in E. coli and show by liquid state NMR that they are properly folded. Kinetic characterization reveals that the C-terminal domain, which contains the substrate-binding pocket, is completely inactive while the N-terminal domain with the two-metal-ion-center and the core catalytic residues exhibits significant activity, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The main function of UshA was therefore proposed to be as a metabolic enzyme. Thereafter, it was demonstrated that NTP, NDP, NMP, and nucleotide sugars were also UshA substrates, but the biological function of this enzyme remains unclear (39,42).…”
Section: Discussionmentioning
confidence: 99%
“…The main function of UshA was therefore proposed to be as a metabolic enzyme. Thereafter, it was demonstrated that NTP, NDP, NMP, and nucleotide sugars were also UshA substrates, but the biological function of this enzyme remains unclear (39,42).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental procedure is detailed in the supplement. Briefly, after expression in E. coli and chromatographic purification (Schultz-Heienbrok et al, 2004; Krug et al, 2013), a tenfold excess of MTSSL over protein was added in two steps with incubation at room temperature and 4°C. Unreacted spin label was removed by a desalting column.…”
Section: Methodsmentioning
confidence: 99%
“…It is a two-domain enzyme with a dimetal center located in the N-terminal domain where various substrates including nucleotides, nucleotide sugars or dinucleotides are hydrolyzed (Glaser et al, 1967; Neu, 1967; Ruiz et al, 1989; Knöfel and Sträter, 1999, 2001b; Schultz-Heienbrok et al, 2005; Krug et al, 2013). Substrates bind to the C-terminal domain in the open state and a 96° rotation of this domain around its center enables hydrolysis via formation of the closed state (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…These two domains (the metallophosphoesterase and 5′-nucleotidase domains) are linked by an α-helix. The molecular structures and catalytic mechanisms of enzymes of this type were thoroughly investigated with Escherichia coli UshA used as a representative (Knofel and Strater 2001 ; Krug et al 2013 ). The C-terminal domain is responsible for binding the substrate base, while the N-terminal domain is responsible for the core catalytic steps.…”
Section: Classification Of Microbial 5′-nucleotidases Their Molecular Structures and Preferable Substratesmentioning
confidence: 99%